Features of behavior of electrons of plasma in open trap in condition of transverse input of powerful microwave pulses at ECR - Antonov, A.N.; Antipov, V.S.; Kornilov, E.A.; Vinokurov, V.A. (Вопросы атомной науки и техники, 2018)
It has been experimentally shown that the effect of oscillations of large amplitude on the frequency of electron
cyclotron resonance on a plasma held by a magnetic trap leads to an effective acceleration of the plasma electrons
and the formation of directed electron fluxes, which in turn stimulate repeated microwave oscillations. A consequence of such a process is the appearance of alternating pulses of microwave oscillations in time. Експериментально показано, що вплив коливань великої амплітуди на частоті електронноциклотронного резонансу на плазму, що утримується магнітною пасткою, призводить до ефективного прискорення електронів плазми і формування направлених потоків електронів, які, в свою чергу, збуджують повторні НВЧ-коливання. Наслідком такого процесу є поява імпульсів НВЧ-коливань, які чергуються в часі. Экспериментально показано, что воздействие колебаний большой амплитуды на частоте электронноциклотронного резонанса на плазму, удерживаемою магнитной ловушкой, приводит к эффективному ускорению электронов плазмы и формированию направленных потоков электронов, которые, в свою очередь,
возбуждают повторные СВЧ-колебания. Следствием такого процесса является появление чередующихся во
времени импульсов СВЧ-колебаний.